Hans Eijkelboom : A meeting on the street. (Amsterdam : NEROC VGM Amsterdam, 2003)
Hans took the inspiration for his meeting from the work NEROC VGM makes for many high-street fashion stores. Hans wanted to capture the relationships, tensions and subtile differences between mothers and daughters of four different European capital cities as they went through the almost universal initiation called The Saturday Shopping Trip. All photographs were taken on consecutive Saturdays. Hans went to Amsterdam, Paris, Berlin and then London. To capture the shopping mothers and daughters in the most natural way. Hans posed as a tourist with a large camera around his neck and a shutter hidden in his pocket. With this technique, he has managed to create an almost hypnotic rhythm. But the deeper you look, the more peculiarities you will notice, especially between the four cities. It seems that, no matter how close-knit Europe gets, even a simple shopping trip can show that the cultural differences are still many miles, or kilometres, apart.
Engels
boek
Keywords: Eijkelboom, Hans